Embraced : You, Me, and Moltmann. - Buchanan, Mark French (Wipf and Stock Publishers, 2015)
In Embraced: Many Stories, One Destiny, Mark Buchanan creatively uses the art of storytelling to illustrate the theology of Jürgen Moltmann. Pastor Buchanan beckons us to engage with the stories and be drawn into a future beyond what we could imagine or create. We are invited to walk with an orphan, a disheartened young adult, a sorrowful community, a frustrated parent, and others, to encounter our own emptiness and indifference and eventually discover that "in the end, a beginning lies hidden." God's boundless resolve to comfort the suffering, gather the lost, bring hope to the despairing, and share life that rises out of death is artfully expressed. Mark Buchanan captures common human experiences and compassionately takes us on the journey from hopelessness into hopefulness. He invites us into the embrace of God that sets us free and unites our story with God's story. As a practical application of Jürgen Moltmann's theology, Embraced: Many Stories, One Destiny introduces us to a shared life with God that is inclusive, hopeful, and creative.